CO2 adsorption study on primary, secondary and tertiary amine functionalized Si-MCM-41. (August 2016) - Ahmed, Sohail; Ramli, Anita; Yusup, Suzana
Highlights: Si-MCM-41 functionalization with amines (MEA, DEA and TEA) by impregnation method. Impact of amine loading and amine type on Si-MCM-41 for CO2 adsorption. Effect of temperature on CO2 adsorption capacity of amine-functionalized Si-MCM-41. CO2 adsorption decreased in order of MEA-, DEA- and TEA-functionalized Si-MCM-41. FTIR analysis of CO2 -saturated MEA-, DEA- and TEA-functionalized Si-MCM-41 samples. Abstract: The present study was conducted to investigate the CO2 adsorption efficiency of siliceous mesoporous material known Si-MCM-41 and impacts of amine loading, amine type, CO2 pressure and adsorption temperatures on CO2 adsorption. Si-MCM-41 was impregnated with monoethanolamine (MEA), diethanolamine (DEA) and triethanolamine (TEA). The adsorption study was investigated from very low pressure to 1 bar at three temperatures ( i.e. 25, 50 and 75 °C) in pure CO2 atmosphere. Pristine Si-MCM-41 shows maximum CO2 adsorption capacity of 27.78 mg/g at 25 °C and 1 bar pressure. Monoethanolamine functionalized Si-MCM-41 with 10–50 wt.% samples were investigated in order to optimize MEA loading for maximum CO2 adsorption. The 50 wt.% MEA-Si-MCM-41 sample exhibited the highest CO2 adsorption capacity of 39.26 mg/g at 25 °C and 1 bar pressure as compared to other samples. 50 wt.% DEA-Si-MCM-41 and 50 wt.% TEA-Si-MCM-41 samples were also investigated for their affinity to capture CO2 at the same conditions. Results show that 50 wt.% MEA-Si-MCM-41 still gives the highest CO2 adsorption capacity while adsorption capacity decreased in order of monoethanolamine, diethanolamine and triethanolamine-functionalized Si-MCM-41. CO2 adsorption capacity of all adsorbents decreases with increasing adsorption temperature above 25 °C. Fourier transform infrared spectroscopy (FTIR) analysis of CO2 -saturated 50 wt.% MEA, DEA and TEA-Si-MCM-41 samples shows the presence of transmission peaks associated to formation of carbamates.